2022
DOI: 10.1111/dewb.12339
|View full text |Cite
|
Sign up to set email alerts
|

Level and determinants of willingness to donate organs among the general public: A cross‐sectional survey in China

Abstract: Background: This study aims to assess the level and determinants of the general public's willingness to organ donation.Methods: We conducted a population-based cross-sectional study of 4261 participants in China. The primary outcome was the willingness to donate organs. Logistic regression modelling was used to determine the factors that affect willingness to donate organs.Results: Overall, the proportion of participants who showed a willingness to donate organs was 47.45% (95%CI: 0.46, 0.49) in this study. Lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…Consistent with many other studies (Al‐Jumah & Abolfotouh, 2011; Chen et al, 2006; Fan et al, 2022; Hernández Rivera et al, 2020; Liu et al, 2020), our study found that female participants are more likely to donate organs compared to male participants. The difference between the personality of man and woman may cause this difference.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with many other studies (Al‐Jumah & Abolfotouh, 2011; Chen et al, 2006; Fan et al, 2022; Hernández Rivera et al, 2020; Liu et al, 2020), our study found that female participants are more likely to donate organs compared to male participants. The difference between the personality of man and woman may cause this difference.…”
Section: Discussionsupporting
confidence: 92%
“…The health literacy questionnaire score was positively related to the donation will. & Abolfotouh, 2011;Fan et al, 2022). Consistent results were observed in blood donors (Chen et al, 2006;Dibaba et al, 2020;Liu et al, 2020).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations